An Ultra-Wideband Antenna with Triple Band-Notched Characteristics for Wearable Application - Rashid, M. A. A.; Shah, S. M.; Majid, H. A.; Musa, U.; Suriani, N. S. (International Journal of Integrated Engineering, 2024)
This work presents a compact UWB antenna with triple band-notched at WiMAX (3.2 GHz to 3.7 GHz), C-band (3.7 GHz to 4.2 GHz) and WLAN (5.15 GHz to 5.35 GHz) for wearable applications. The UWB antenna is fabricated on a semi-flexible thin FR-4 substrate. In order to reduce the complexity, only two slots are introduced on the radiating patch instead of three slots to reject each narrowband frequency. In this case, one slot rejects a combination of WiMAX and C-band and the other slot rejects the WLAN frequency band. The UWB antenna on the thin FR-4 material has an overall size of 21×16 mm2, which is very compact and thus, suitable for wearable applications without causing discomfort when worn on-body. Although the antenna is small in size, the performance is not compromised. The UWB antenna has the frequency range from 2.51 GHz to 12.09 GHz, maximum radiation efficiency of 100% and maximum gain of 4 dBi. Nevertheless, the antenna is able to reject the WiMAX and C-band as well as the WLAN band. The simulated Specific Absorption Rate (SAR) results show that the antenna complies with the SAR limit Federal Communication Commission (FCC) and International Commission of Non-Ionizing Radiation Protections (ICNIRP) standards for 1 mW input power. Bending investigations performed on different diameters of Styrofoam cylinders shows that the frequency range and the notch bands are not very much affected.